Settled dust assessment in clinical environment: useful for the evaluation of a wider bioburden spectrum - Viegas, Carla (2019)
Project EXPOsE – Establishing protocols to assess occupational exposure to microbiota in clinical settings. Project nº 23222 (02/SAICT/2016).